The safety of induced sputum collection in infants under the age of 18 months - H. van Wyk; R. Jacquemard; G. Joubert (AOSIS, 2001)
The technique of sputum induction improves the yield of microbiological investigations for organisms such as Mycobacterium tuberculosis and Pneumocystis carinii. The aim of the study was to determine the safety of this method in children under the age of 18 months. Heart rate and oxygen saturation were monitored during the procedure and compared with measurements obtained during the conventional method of sputum collection in the same patients. Patients were also observed for other possible side effects. Forty samples of sputa were obtained from 20 patients. No clinical differences in heart rate and oxygen saturation were found between the two methods. Overall, oxygen saturation measurements below 80% were recorded in three patients. Increased coughing and mild epistaxis did occur more frequently during the sputum induction method. It was concluded that sputum induction is safe in small children, but a larger sample size needs to be studied.